Sources of value creation in service global value chains - Metka Stare; Andreja Jaklič (Amfiteatru Economic Journal, 2020)
Multiple dimensions of services and service functions in global value chains (GVCs) are not sufficiently explored, particularly so when considering the perspective of Central and East European (CEE) countries as suppliers of services. A comprehensive conceptual framework for the analysis of GVCs is missing as well. The main objective of the paper is to uncover the sources and dynamic of value creation process in service GVCs and identify what makes the ascending value creation in service GVCs possible. Based on case studies exploratory analysis of service GVCs we propose a novel conceptualization of value creation in service GVCs and introduce a new model of spiral dynamic of value creation. The findings show that firms using combination of different value creation logics benefit from multiplying and mastering role of services in GVCs. These findings have implications for service management and value chain strategy beyond service industries and CEE region.
Keywords: F23; F61; L23; L80; O52; 330; service GVC; network-based capabilities; value creation; model of spiral value creation; Central and Eastern Europe (CEE)